Thermotrophy Exploratory Study - Lee, James Weifu (Journal of Scientific Exploration, 2023)
The question of whether environmental heat energy could be utilized as a source of energy for biological metabolism is the center of this exploratory research. In 1979, this author postulated a hypothesis for the existence of thermotrophs that could isothermally utilize environmental heat energy as a source of their energy on Earth. According to this hypothesis, the thermotrophs could be the first primitive forms of life in the early Earth environment. The chemotrophs and phototrophs that we currently are all well familiar with might have been evolved somehow from the primitive thermotrophs. Furthermore, all the organisms currently regarded as the “chemotrophs” and “phototrophs” could actually be the mixed trophy types containing thermotrophic features: thermo-chemotrophs and thermo-phototrophs. Energetic analysis with the thermodynamic first law indicated that the anaerobic acetate-utilizing methanogenic archaea Methanosarcina could be a “living fossil specimen” of the thermotrophs. Experiments with enriched acetate-utilizing methanogen including Methanosarcina has, for the first time, demonstrated that their anaerobic metabolism was indeed associated with isothermal environmental heat utilization, resulting in their liquid culture temperature to change (decrease) by about −0.10 oC and sometimes drop by as much as −0.45 oC observed in the experiments. The mean temperature change (drop) was −0.25 ±0.06 oC